Protection Against Invasive Infections in Children Caused by Encapsulated Bacteria - Sadarangani, Manish (Frontiers in Immunology, 2018)
The encapsulated bacteria Streptococcus pneumoniae, Neisseria meningitis, Haemophilus influenzae and Streptococcus agalactiae (Group B Streptococcus) have been responsible for the majority of severe infections in children for decades, specifically bacteremia and meningitis. Isolates which cause invasive disease are usually surrounded by a polysaccharide capsule, which is a major virulence factor and the key antigen in protective protein-polysaccharide conjugate vaccines. Protection against these bacteria is largely mediated via polysaccharide-specific antibody and complement, although the contribution of these and other components, and the precise mechanisms, vary between species and include opsonophagocytosis and complement-dependent bacteriolysis. Further studies are required to more precisely elucidate mechanisms of protection against non-type b H. influenzae and Group B Streptococcus.